Factors That Affect Overtime Work and Employees Motivation In Restaurant Bebek Sultan Pattimura Dumai - Lastari Nabila; Nageeta Tara Rosa (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2025)
The research was carried out at the Restaurant Bebek Sultan Patimura Dumai, this research aims to find out Factors that Affect Overtime Work and Employee Motivation, this research is a qualitative descriptive evaluation, and data collection is done through interviews and documentation, as for the population and the sample of the study were employees of Restaurant Bebek Sultan Patimura Dumai which numbered 12 people. The results of this study prove that employees work overtime and do not get bonuses, and the motivation of employees depends on each individual. The factor of overtime work greatly affects employee motivation, resulting in fatigue and potentially reducing the quality of employee work life. The imbalance between workload and rest time can physically and mentally harm employees, reducing enthusiasm and satisfaction at work. In addition, the negative impact on employees' health and physique can affect productivity and cause a decrease in morale. Therefore, Restaurants need to pay attention to employee needs between work and rest time to increase employee motivation and overall work comfort.